The Visual dictionary of ancient civilizations. (Boston : Distributed by Houghton Mifflin, 1994)
Depicts the great civilizations of the ancient world, describing art, artifacts and architecture.
Includes index.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
6.9.
6.9
Keywords: Civilization, Ancient -- Dictionaries; Civilization, Ancient -- Pictorial works; Civilization, Ancient -- Dictionaries; Civilization, Ancient -- Pictorial works; Ancient civilization -- Dictionaries; Ancient civilization -- Pictorial works